2017
DOI: 10.1021/acs.analchem.7b01856
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Sensitive Potentiometric Measurements of Dilute Redox Molecule Solutions and Determination of Sensitivity Factors at Platinum Ultramicroelectrodes

Abstract: Open circuit potential (OCP) measurements can be very sensitive to small changes in the electrode environment and may allow detection of electron transfer events involving few, and maybe single, electrons. Factors affecting the overall sensitivity of OCP measurements were investigated to achieve the highest sensitivity. The OCP of platinum ultramicroelectrodes (UMEs) was determined in solutions that initially contained only supporting electrolyte where the OCP is a mixed potential governed by background farada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…As stated in the previous sentence, each step is associated with a potential-step experiment except for drop-casting, and these potential–time profiles are also shown in Figure for clarity. The lines around 0.4 V indicate discrepancies in the experimental open-circuit potential, which arise from different species dominating the two half reactions at the electrode surface when the cell is at open circuit …”
Section: Resultsmentioning
confidence: 99%
“…As stated in the previous sentence, each step is associated with a potential-step experiment except for drop-casting, and these potential–time profiles are also shown in Figure for clarity. The lines around 0.4 V indicate discrepancies in the experimental open-circuit potential, which arise from different species dominating the two half reactions at the electrode surface when the cell is at open circuit …”
Section: Resultsmentioning
confidence: 99%
“…Here an open circuit potential detection of single metal nanoparticle collisions was achieved, demonstrating how sensitive even electrochemical potentiometric detections can be. 76,77 Fig. 4 Conceptual structure of a bipolar-junction-transistor based on a PEDOT:PSS OECT serving as an amperometric sensor to detect and amplify the faradaic current generated by the species A undergoing an oxidation process in the base region.…”
Section: The Organic Electrochemical Transistorsmentioning
confidence: 99%
“…The redox couple enables the exchange of charge between a metallic electrode and the solution and aligns the electrochemical potentials. In its absence, the electrode is unpoised: Percival and Bard 37 have shown that the open circuit potential (OCP) varies between ~0 V for a de-aerated solution and 520 mV/NHE for an air-saturated one. The redox couple provides us with a crucial thermodynamic quantity, ∆ r G red/ox sol the (positive) Gibbs energy change (eV/particle) of the oxidation reaction red → ox +e in vacuum at rest at infinity.…”
Section: Thermodynamics and Fermi Level Alignmentmentioning
confidence: 99%
“…In the absence of a well-defined ferricyanide/ferrocyanide redox couple, the determination of λ OX is normally impracticable, because the electronic levels of water, and in particular the binding energy of the ferrocyanide solute, can be fixed by some unknown "background" couple (see ref 37 ). Nonetheless, considering a solution with the ferrocyanide ion alone, Seidel et al have calculated a λ OX value of 1.47 eV.…”
Section: {9}mentioning
confidence: 99%
See 1 more Smart Citation